2012
DOI: 10.1007/s11255-012-0244-7
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-related infections in chronic hemodialysis: a clinical and economic perspective

Abstract: Despite the limitations resulting from retrospective cross-sectional single-center design, our study suggests that patients already on HD who required catheters as bridge angioaccess were more prone to bacteremia. This highlights the importance of close angioaccess monitoring to avoid unnecessary catheter usage. A similar increase in costs when initiating dialysis on catheter as in case of complicated bacteremia strongly supports the initial placement of a native arteriovenous fistula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
1
12
2
Order By: Relevance
“…This result is consistent with other reports showing end-stage renal failure is a risk factor of MRSA colonisation, infection and infection-related mortality. 2530 Within the nested cohort of our patients who were either colonised or infected with MSSA/MRSA, the MRSA infection rate among those with end-stage renal failure was high (14/54; 26%) compared to those without end-stage renal failure (73/668; 12.3%). If our results are confirmed by other Australian ICUs, perhaps empirical vancomycin therapy should be considered in critically ill patients who have end-stage renal failure when serious systemic infection or bacteraemia is suspected, especially if they are known to be colonised with MRSA, or in centres where MRSA infection is endemic.…”
Section: Discussionmentioning
confidence: 92%
“…This result is consistent with other reports showing end-stage renal failure is a risk factor of MRSA colonisation, infection and infection-related mortality. 2530 Within the nested cohort of our patients who were either colonised or infected with MSSA/MRSA, the MRSA infection rate among those with end-stage renal failure was high (14/54; 26%) compared to those without end-stage renal failure (73/668; 12.3%). If our results are confirmed by other Australian ICUs, perhaps empirical vancomycin therapy should be considered in critically ill patients who have end-stage renal failure when serious systemic infection or bacteraemia is suspected, especially if they are known to be colonised with MRSA, or in centres where MRSA infection is endemic.…”
Section: Discussionmentioning
confidence: 92%
“…It is well grounded in the literature that the catheter as access for HD, is associated with increased infections, and higher morbidity and mortality [18,19]. A study by Taylor, et al found that the relative risk of bacteremia in those using catheter for HD was estimated to be ten times greater than in patients with AVF.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, CMV-specific CD4 + T cells represent 4% and 9.1% of total and memory T lymphocyte pools, respectively. 65 After a primary infection, CMV-specific CD4 + T cells can be detected from 7 to 10 days after the occurrence of viremia in SOTR, 66 and a delay in CD4 + T cell expansion is correlated with the severity of the disease.…”
Section: Cmv-specific Cd4 + T Cellsmentioning
confidence: 99%